Chronic hepatitis C virus infection: Serum biomarkers in predicting liver damage - Valva, Pamela (2016)
Currently, a major clinical challenge in the management of the increasing number of hepatitis C virus (HCV) infected patients is determining the best means for evaluating liver impairment. Prognosis and treatment of chronic hepatitis C (CHC) are partly dependent on the assessment of histological activity, namely cell necrosis and inflammation, and the degree of liver fibrosis. These parameters can be provided by liver biopsy; however, in addition to the risks related to an invasive procedure, liver biopsy has been associated with sampling error mostly due to suboptimal biopsy size. To avoid these pitfalls, several markers have been proposed as non-invasive alternatives for the diagnosis of liver damage. Distinct approaches among the currently available non-invasive methods are (1) the physical ones based on imaging techniques; and (2) the biological ones based on serum biomarkers. In this review, we discuss these approaches with special focus on currently available non-invasive serum markers. We will discuss: (1) class I serum biomarkers individually and as combined panels, particularly those that mirror the metabolism of liver extracellular matrix turnover and/or fibrogenic cell changes; (2) class II biomarkers that are indirect serum markers and are based on the evaluation of common functional alterations in the liver; and (3) biomarkers of liver cell death, since hepatocyte apoptosis plays a significant role in the pathogenesis of HCV infection. We highlight in this review the evidence behind the use of these markers and assess the diagnostic accuracy as well as advantages, limitations, and application in clinical practice of each test for predicting liver damage in CHC.